The Hospital Anxiety and Depression Scale (HADS) and the 9-item Patient Health Questionnaire (PHQ-9) as screening instruments for depression in patients with cancer - Hartung, Tim J.; Keller, Monika (Cancer, 2017)
BACKGROUND Depression screening in patients with cancer is recommended by major clinical guidelines, although the evidence on individual screening tools is limited for this population. Here, the authors assess and compare the diagnostic accuracy of 2 established screening instruments: the depression modules of the 9-item Patient Health Questionnaire (PHQ-9) and the Hospital Anxiety and Depression Scale (HADS-D), in a representative sample of patients with cancer. METHODS This multicenter study was conducted with a proportional, stratified, random sample of 2141 patients with cancer across all major tumor sites and treatment settings. The PHQ-9 and HADS-D were assessed and compared in terms of diagnostic accuracy and receiver operating characteristic (ROC) curves for Diagnostic and Statistical Manual of Mental Disorders, 4th edition diagnosis of major depressive disorder using the Composite International Diagnostic Interview for Oncology as the criterion standard. RESULTS The diagnostic accuracy of the PHQ-9 and HADS-D was fair for diagnosing major depressive disorder, with areas under the ROC curves of 0.78 (95% confidence interval, 0.76-0.79) and 0.75 (95% confidence interval, 0.74-0.77), respectively. The 2 questionnaires did not differ significantly in their areas under the ROC curves (P = .15). The PHQ-9 with a cutoff score ≥7 had the best screening performance, with a sensitivity of 83% (95% confidence interval, 78%-89%) and a specificity of 61% (95% confidence interval, 59%-63%). The American Society of Clinical Oncology guideline screening algorithm had a sensitivity of 44% (95% confidence interval, 36%-51%) and a specificity of 84% (95% confidence interval, 83%-85%). CONCLUSIONS In patients with cancer, the screening performance of both the PHQ-9 and the HADS-D was limited compared with a standardized diagnostic interview. Costs and benefits of routinely screening all patients with cancer should be weighed carefully. Cancer 2017;123:4236-4243. © 2017 American Cancer Society.